Integrated STEM education: addressing theoretical ambiguities and practical applications - Portillo-Blanco, Ane; Guisasola, Jenaro; Zuza, Kristina (Frontiers in Education, 2025)
Integrated STEM education (iSTEM) has become an innovative educational strategy that combines Science, Technology, Engineering, and Mathematics to address contemporary scientific and technical challenges. Yet, the variety of interpretations of the theoretical foundations of iSTEM education makes its understanding, analysis, and translation into classroom reality a complicated process. This article explores the foundations of iSTEM education by analyzing key systematic reviews that identify and describe the most widely agreed upon principles, with five: integration, real-world problems, inquiry, design, and cooperative work. Even so, the explanations in the literature reviewed do not clarify the relationship between them. Debate arises about their hierarchy and relative importance in the design of Teaching-Learning Sequences. The review of this study highlights that integration and the use of real-world problems are fundamental pillars, while other principles, such as inquiry and design, vary according to the disciplinary approach. The article also addresses the impact of problem choice on teaching strategies to understand the relationship between the principles of “real-world problem,” “design,” and “inquiry.” Thus, epistemological differences between Science, Mathematics, and Engineering determine how an iSTEM problem is defined and solved, with Science and Engineering leading the way in problem formulation due to their wide use in the literature. This allows for the analysis of Design-Based Learning (DBL) and Inquiry-Based Learning (IBL) as the main teaching approaches and presents a range of problem types to be used in the classroom depending on the objective pursued. Finally, this study highlights the need to connect the theoretical foundations with their practical application in actual teaching-learning sequences, providing a framework for future research to enrich the understanding and application of iSTEM education.